A inclusão de alunos surdos na educação de Jovens e Adultos (EJA - COSTA, Karla Cyrlene De Souza Da (Universidade Federal do Tocantins, 2023)
This research has as its theme the inclusion of deaf students in the education of young people and adults (EJA). This is a research with a qualitative approach, using action research as a strategy. The general objective is to list and analyze what were the contributions that occurred during the inclusion process of deaf students in the EJA, considering, among other aspects, the teacher's education and pedagogical conceptions about inclusion. The research was carried out in two municipal public schools in the southern region of the city of Palmas-Tocantins, in order to map whether, between the years 2010 and 2019, there was a search for vacancies for deaf students to enroll in the modality of the EJA, if any student was enrolled and if this student attended and was able to complete their studies. To know the reality of these schools, semi-structured interviews were conducted with the coordinators, teachers, sign language interpreters, deaf students and family. The interviews revealed indications of the absence of educational practices aimed at deaf students and pedagogical practices aimed only at hearing students. Such practices could cover everyone so that there is no exclusion of those who are the subjects in the teaching and learning process.